2015
DOI: 10.1186/s40814-015-0021-3
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic cued motor imagery and walking in people with multiple sclerosis: a randomised controlled feasibility study

Abstract: BackgroundNovel physiotherapy approaches such as motor imagery and rhythmic auditory stimulation have been shown to improve walking in people with multiple sclerosis (MS). Rhythmic cued motor imagery was used in this study, whose objectives were to evaluate the feasibility of a larger randomised controlled trial (RCT) in people with MS and to obtain information on walking.MethodsThirty adult people with MS who scored 1.5–4.5 on the Expanded Disability Status Scale were recruited at the MS Clinic Innsbruck, Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 57 publications
1
22
1
4
Order By: Relevance
“…Our study could have used this patient-rated questionnaire, but our participants were called weekly to ask for any problems with kinaesthetic motor imagery, and they were supported accordingly. In addition, all motor imagery ability studies in people with MS were experimental studies with no long-term training effects, in contrast to our 4 weeks duration study with 24 training sessions which might have enhanced the mental representation [68]. ”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study could have used this patient-rated questionnaire, but our participants were called weekly to ask for any problems with kinaesthetic motor imagery, and they were supported accordingly. In addition, all motor imagery ability studies in people with MS were experimental studies with no long-term training effects, in contrast to our 4 weeks duration study with 24 training sessions which might have enhanced the mental representation [68]. ”…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nature of this feasibility study, it was decided not to conduct any efficacy statistical tests on the walking and fatigue data [68]. ”…”
Section: Methodsmentioning
confidence: 99%
“…Another crucial aspect analyzed in the current review is the effects of auditory cueing induced mental imagery in patients multiple sclerosis ( 71 , 70 ). Labriffe et al ( 126 ) reported higher activations in primary sensorimotor cortex and secondary somatosensory cortex bilaterally during the imagination of gait.…”
Section: Discussionmentioning
confidence: 99%
“…Medians (range) were reported for ordinal data (fatigue), mean (95% confidence interval (CI)) were reported for continuous data (walking speed and walking distance) and raw count (number, %) was reported for nominal data. Due to the nature of this feasibility study, it was decided not to conduct any efficacy statistical tests on the walking and fatigue data.” 68 …”
Section: Extension Of Consort 2010 To Pilot Trialsmentioning
confidence: 99%